2015
DOI: 10.1038/ngeo2458
|View full text |Cite
|
Sign up to set email alerts
|

Computational support for a pyrolitic lower mantle containing ferric iron

Abstract: The dominant minerals in Earth's lower mantle are thought to be Fe-and Al-bearing MgSiO 3 bridgmanite and (Mg,Fe)O ferropericlase 1 . However, experimental measurements of the elasticity of these minerals at realistic lower-mantle pressures and temperatures remain impractical. As a result, di erent compositional models for the Earth's lower mantle have been proposed 2-4 . Theoretical simulations, which depend on empirical evaluations of the e ects of Fe incorporation into these minerals, support a pyrolitic lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
71
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 41 publications
2
71
1
Order By: Relevance
“…Although previous studies suggested that even a small amount of CaPv can be a seismologically visible component in the LM, a relatively similar [Wang et al, 2014]. Black dots indicate the PREM values [Dziewonski and Anderson, 1981].…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
See 3 more Smart Citations
“…Although previous studies suggested that even a small amount of CaPv can be a seismologically visible component in the LM, a relatively similar [Wang et al, 2014]. Black dots indicate the PREM values [Dziewonski and Anderson, 1981].…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
“…Pluses are values before a pressure correction by Li et al [2006b]. Velocities and densities of 12.5 mol % Fe-bearing MgPv at 2000 and 3000 K are also shown as a reference (dashed lines) [Wang et al, 2014]. (d) Azimuthal anisotropy for longitudinal (A P ) and shear (A S ) waves as a function of pressure at 1000, 2000, 3000, and 4000 K. (colored lines).…”
Section: /2015gl063446mentioning
confidence: 99%
See 2 more Smart Citations
“…They argue that such a relict of the banded iron formation may explain the observed features of the ultralow-velocity zones of the seismic wave on the core-mantle boundary. A recent theoretical study showed that the seismic wave velocity in the lower mantle can be explained by the existence of ferric iron (Wang et al, 2015). It is expected that iron oxide hydroxide may be formed when the banded iron formations along with the oceanic crust subducted into the mantle.…”
mentioning
confidence: 99%